Methods using block copolymer self-assembly for sub-lithographic patterning - MILLWARD DAN B (2008)
Block copolymers can be self-assembled and used in methods as described herein for sub-lithographic patterning, for example. The block copolymers can be diblock copolymers, triblock copolymers, multiblock copolymers, or combinations thereof. Such methods can be useful for making devices that include, for example, sub-lithographic conductive lines.